TEACHING PAST TENSE THROUGH DISCUSSION TECHNIQUE - Rizky Mirani Desi Pratama (Wanastra: Jurnal Bahasa dan Sastra, 2014)
Grammar is central to the teaching and learning of languages. Grammar helps us in several phenomena.For example, if we want to translate sentence or paragraph into English, we need grammar in order to the meaning is clear and easy to understand. Grammar is often taught and learnt by every grade or level at a school or a course. Grammar is also one of difficult aspects of language to teach well. Because of that, the teacher must have the solution. Teacher has a significant role for this case because he or she is one of mediator of students getting knowledge. Teachers must have some good techniques for teaching grammar especially past tense, for example discussion. A research to know the effectiveness of teaching English Past Tense trough Discussion technique hasbeen conducted at the third grade of SD Pelita Insani Bogor. The data were collected through observation, intreview, teaching-learning process, pre-test and post-test. The implementation of technique was the students had to discuss about past tense material which has been prepared by the teacher in a group. Discussion technique makes the students share their knowledge with their friends. Using discussion can make the third grade students in SD Pelita Insani Bogor more easily understanding and using past tense correctly. The students of Pelita Insani also can do the post-test which is a mean to evaluate the technique and teaching-learning process well and become more active in the teaching-learning process. The result of the post-test showed that teaching English pasttense through discussion technique is one of good solution to improve the Pelita Insani’s students’ comprehend about past tense.